The Lead Exposure Risk Due to Wells Water Consumption in Code Riverside Community, Yogyakarta City (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
The environmental conditions of Code River were strongly influenced by anthropogenic activities that include industry, hospitals, domestic, and agriculture. The contamination status on the Code River according to BLH Yogyakarta reported in 2014 was heavily polluted based on STORET (â‰¤-31). The riverside community were misusing the river for final disposal site, potentially contaminating it with lead (Pb). Local communities were potentially exposed to Pb toxicity through well water consumption. An Environmental Health Risk Assessment (EHRA) study of ingestion exposure of heavy metals was never conducted in the Code Riverside, making itÂ  interesting for further studies. The study aimed to determine human health risks of consumption of well water containing Pb in Code Riverside, Yogyakarta City using an observational design with an Environmental Health Risk Assessment approach. There were 9 environmental samples and 47 respondents selected based on certain criteria. Data was collected through environmental inspection and human health assessment, interviews and anthropometric data measurement of respondents. Data was analyzed by univariate (frequency distribution) and EHRA methods. The result showed that the noncarcinogenic risk level of Pb due to well water consumption from majority of research sites have RQ value (Risk Quotient) 1, which means high potential risk to human health.